2013
DOI: 10.4236/jgis.2013.56055
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Modeling for Sinkholes Hazard Map Based on GIS & RS Data

Abstract: The Kinta Valley is an area of karst in the north-western part of Peninsular Malaysia. Over 30 years of uncontrolled land use and development has led to significant changes in topography and geomorphology, such as the appearance of sinkholes. In this paper, geospatial techniques were utilized to the task of evaluating sinkholes susceptibility map using a spatial multi criteria evaluation approach (SMCE). Sinkhole location and a spatial database were applied to calculate eight inherent causative factors for lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
(15 reference statements)
0
17
0
1
Order By: Relevance
“…For example, during intense rainfall events, the underlying soils and steep slopes often destabilise and can result in devastating landslides with significant loss of life and economic cost (Kometa and Akoh 2012, Akpan et al 2015, Laribi et al 2015. The depletion of groundwater via overpumping can also trigger the emergence of large sinkholes by removing the supporting buoyancy of groundwater, resulting in the emergence of underground cavities beneath densely populated urban areas (Al-Kouri et al 2013). There is therefore a pressing need for more pragmatic landscape planning and groundwater management in developing countries, owing to the high geomorphological risk associated with a lack of regulation in these areas.…”
Section: Physical/geomorphic Impactsmentioning
confidence: 99%
“…For example, during intense rainfall events, the underlying soils and steep slopes often destabilise and can result in devastating landslides with significant loss of life and economic cost (Kometa and Akoh 2012, Akpan et al 2015, Laribi et al 2015. The depletion of groundwater via overpumping can also trigger the emergence of large sinkholes by removing the supporting buoyancy of groundwater, resulting in the emergence of underground cavities beneath densely populated urban areas (Al-Kouri et al 2013). There is therefore a pressing need for more pragmatic landscape planning and groundwater management in developing countries, owing to the high geomorphological risk associated with a lack of regulation in these areas.…”
Section: Physical/geomorphic Impactsmentioning
confidence: 99%
“…The purpose of developing a statistical model is to generate a hazard map that shows the level of risks, taking into account various critical factors identified. Several researches have established sinkhole hazard models incorporating various data interpretation techniques [1,4,5]. The sinkhole hazard models, suggested from previous studies, highly depend on the degree of event occurrences.…”
Section: Develop a Statistical Modelmentioning
confidence: 99%
“…It should be noted that the sinkhole is different from underground cavities, dealt with in this article. Several researches have reported that sinkhole hazard is common in limestone karst, associated with subcircular surface depression or collapse structure formed by the collapse of small subterranean karst cavities [1,2]. Therefore it is deemed more likely a natural phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Research by (Kouri, et al, 2013) used statistical method associated with GIS and remote sensing data to produce sinkholes hazard map in Kinta Valley, Perak. Eight causative parameters were used namely lithology, structure (lineament), soil cover, slope, land use mining, urban area features, ponds and rivers.…”
Section: Multi-criteria Decision Making Techniques (Mcdm)mentioning
confidence: 99%
“…The AHP technique is developed by Saaty is based on three principles namely: decomposition, comparative judgment and synthesis of priorities (Malczewski, 1999). The use of GIS allows the combination of data from various sources gives the higher accuracy and time efficient (Kouri, et al, 2013). Inaccurate prediction will cause the human ignorance, then, more sinkhole to occur.…”
Section: Introductionmentioning
confidence: 99%